The Groebke–Blackburn–Bienaymé reaction in its maturity: innovation and improvements since its 21st birthday (2019–2023) - Martini, Cristina; Mardjan, Muhammad Idham Darussalam; Basso, Andrea (Beilstein Journal of Organic Chemistry, 2024)
The Groebke–Blackburn–Bienaymé (GBB) three-component reaction, discovered in 1998, is a very efficient strategy to assemble imidazo[1,2-a]-heterocycles starting from amidines, aldehydes and isocyanides. This review aims to exhaustively describe innovative aspects of this reaction achieved during the last five years, and classifies them into five categories: synthetic methods, building blocks, scaffolds, biological activities and physical properties.
Keywords: Groebke–Blackburn–Bienaymé reaction; multicomponent reactions; heterocycles; imidazo[1,2-a]pyridines; isocyanides